Penerapan manajemen resiko kepatuhan dan hukum pada bank syariah - Asari, Fahreza Naafi (Maliki Interdisciplinary Journal, 2024)
Legal risk and compliance risk are two forms of threats that can endanger the stability of Islamic banks. Sharia banks whose basic procedures and products are based on Islamic law certainly require caution in their formation. These two risks arise due to weaknesses, violations and non-conformities related to applicable laws and regulations. For sharia banks, the institution entitled to carry out supervisory and enforcement duties is the Sharia Supervisory Board which also issues fatwas that sharia banks need to comply with. With the nature of risk that cannot be eliminated, efforts are needed to minimize the negative impact of the two risks faced, namely legal risk and compliance risk. The effort in question is carrying out risk management activities which aim to identify, measure and overcome the risks faced by Islamic banks. Therefore, this literature study focuses on the application of risk management, namely compliance risk and legal risk, so that by implementing good risk management, banks can overcome and face these risks well.